European LiDAR Mapping Forum Un report dal futuro del 3D intelligente (GEOmedia, 2013)
Circa 450 delegati provenienti da 45 paesi si sono riuniti per lo European LiDAR Mapping Forum (ELMF)al Congress Palace nel centro di Salisburgo in Austria, dove si sono succedute presentazioni da parte diesperti leader a livello mondiale.Abstract About 450 delegates from 45 countries gathered for the European LiDAR Mapping Forum (ELMF) at the Congress Palace in the center of Salzburg in Austria, with presentations by leading experts in the world. The topics on the use of LiDAR to support transport, urban modeling, coastal zone mapping, asset management, 3D visualization and GIS applications, have contributed to the success of the third ELMF (the first took place in 2012 ) from 4 to 5 December 2012.